Usia Ibu dan Hubungannya dengan Kondisi Kehamilan, Persalinan, Postpartum dan Kondisi Neonatal (Journal of Telenursing (JOTING), 2024)
This study analyzes the relationship between maternal age and various aspects of pregnancy, delivery, postpartum conditions, and neonatal outcomes in Indonesia. The research method used was an observational design with a cross-sectional approach. The results showed that there was a significant relationship between maternal age and pregnancy conditions (p